2021
DOI: 10.46743/2160-3715/2021.4004
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Authentic Leadership through Leadership Journey of Gandhi

Abstract: Leadership research will benefit from bringing in the subjective realities of becoming a leader by considering the leadership journey. Generating an understanding of how leaders turn episodes in time into meaningful subjective narratives helps shed light on the meaning-making process. We seek in this inquiry to understand self-awareness with a narrative meaning-making process. In this study, we adopt a narrative research approach for analyzing the autobiography of Mahatma Gandhi, who is widely acknowledged as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…In this study, the support and trust led to a positive outcome: the flourishing of employees. This outcome is similar to previous research that established that authentic behavior had a profound influence on creating supportive workspaces and trust ( Alkaabi, 2018 ; Malik et al, 2020 ), as well as the well-being of employees ( Kernis, 2003 ; Ilies et al, 2005 ; Rautenbach and Rothmann, 2017b ; Kerns, 2018 ; Agarwal, 2021 ; Nair et al, 2021 ), directly or indirectly. What makes these results more significant is that during times of COVID-19, leaders had less time to interact on a one-to-one basis or to demonstrate support and care.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this study, the support and trust led to a positive outcome: the flourishing of employees. This outcome is similar to previous research that established that authentic behavior had a profound influence on creating supportive workspaces and trust ( Alkaabi, 2018 ; Malik et al, 2020 ), as well as the well-being of employees ( Kernis, 2003 ; Ilies et al, 2005 ; Rautenbach and Rothmann, 2017b ; Kerns, 2018 ; Agarwal, 2021 ; Nair et al, 2021 ), directly or indirectly. What makes these results more significant is that during times of COVID-19, leaders had less time to interact on a one-to-one basis or to demonstrate support and care.…”
Section: Discussionsupporting
confidence: 89%
“…Recent studies found that authentic leadership could be beneficial to organizations, as it was associated with a variety of positive end results, such as follower creativity, team member performance ( Duarte et al, 2021 ), consumer focus, personnel retention ( Ribeiro et al, 2020 ), and employee flourishing ( Nair et al, 2021 ; Kleynhans et al, 2022 ). Ryff and Keyes (1995) maintain that when leaders exhibit behavior linked to the dimensions of authentic leadership (self-awareness, internalized moral perspective, balanced processing, and relational transparency), they can influence the well-being of employees.…”
Section: Literature Review and Hypothesismentioning
confidence: 99%
“…Authenticity refers to self-awareness and consistency of inner thoughts, emotions, and values. It consists of two elements: self-awareness and self-regulation [144]. Self-awareness refers to recognizing one's true self at present and is a process of continuously understanding one's talents, strengths, goals, core values, beliefs, and desires.…”
Section: Authentic Leadershipmentioning
confidence: 99%
“…Self-awareness refers to recognizing one's true self at present and is a process of continuously understanding one's talents, strengths, goals, core values, beliefs, and desires. Self-regulation is the process by which a person aligns their behavior with their values and goals [144].…”
Section: Authentic Leadershipmentioning
confidence: 99%
“…Authentic leaders inspire and motivate subordinates to achieve goals through authenticity and positive moral views, aided by enhanced awareness and effective communication (Crawford et al, 2019). Recent research indicated that AL could have a positive impact on organizations as it has been linked to various outcomes, such as individual creativity, individual performance (Duarte et al, 2021), customer orientation, employee retention (Ribeiro et al, 2020), and employee F (Nair et al, 2021). Although AL has been conceptualized in several ways and evaluated in various empirical research studies (Gardner et al, 2011), possibly the most frequently utilized definition is the one posited by Walumbwa et al (2008) as "A pattern of leader behavior that draws upon and promotes both positive psychological capacities and a positive ethical climate to foster greater self-awareness, an internalized moral perspective, balanced processing of information, and relational transparency on the part of leaders working with followers, fostering positive self-development" (p. 94).…”
Section: Literature Review and Hypotheses Authentic Leadershipmentioning
confidence: 99%